2021
DOI: 10.1007/s11906-021-01138-5
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of MicroRNAs in SARS-CoV-2 Infection Comorbid with HIV-Associated Preeclampsia

Abstract: Purpose of Review This review investigated the potential role of microRNAs (miRNAs) in the synergy of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, preeclampsia (PE), and human immunodeficiency virus (HIV) infection. Maternal health is a great concern when treating pregnant women fighting this triad of diseases, which is highly prevalent in South Africa. MicroRNAs are involved in fine-tuning of physiological processes. Disruptions to the balance of this minute protein can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 139 publications
(167 reference statements)
2
7
0
Order By: Relevance
“…miRNA profiled from the human placenta of infected and uninfected control subjects reported the isolation of a number of miRNAs including miR-21b, miR-29c, miR-98, miR-146, miR-155, miR-190, miR-346, and miR-326 which acts in viral replication through direct-indirect mechanisms and could be potential biomarkers [119] . Complications in pregnancy, including in HIV-associated preeclampsia interlinking SARS-CoV-2 and HIV infection, report identification of potential host miRNAs with anti-SARS-CoV-2 infection properties and differential expression including miR-28, miR-125b, miR-150, miR-223, and miR-382 by the studies of Huang, Jialing et al, while Nersisyan et al, studies report miR-21, miR-195-5p, miR-16-5p, miR-3065-5p, miR-424-5p, and miR-421 miRNAs which can be further studied for their HIV-associated preeclampsia and COVID-19 associations [84] , [120] , [121] . Although it is worth mentioning that the lack of studies correlating SARS-CoV-2 infection and its association with miRNA expression profiles in pregnant women significantly constricts the data and therefore warrants further studies in this field in the future.…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
“…miRNA profiled from the human placenta of infected and uninfected control subjects reported the isolation of a number of miRNAs including miR-21b, miR-29c, miR-98, miR-146, miR-155, miR-190, miR-346, and miR-326 which acts in viral replication through direct-indirect mechanisms and could be potential biomarkers [119] . Complications in pregnancy, including in HIV-associated preeclampsia interlinking SARS-CoV-2 and HIV infection, report identification of potential host miRNAs with anti-SARS-CoV-2 infection properties and differential expression including miR-28, miR-125b, miR-150, miR-223, and miR-382 by the studies of Huang, Jialing et al, while Nersisyan et al, studies report miR-21, miR-195-5p, miR-16-5p, miR-3065-5p, miR-424-5p, and miR-421 miRNAs which can be further studied for their HIV-associated preeclampsia and COVID-19 associations [84] , [120] , [121] . Although it is worth mentioning that the lack of studies correlating SARS-CoV-2 infection and its association with miRNA expression profiles in pregnant women significantly constricts the data and therefore warrants further studies in this field in the future.…”
Section: Mirnas As Therapeutic Biomarkermentioning
confidence: 99%
“…They target about 60% of the human genome and may serve as potential biomarkers for many diseases ( Friedman et al, 2009 ). Since miRNAs offer fine-tuning of proteinsynthesis, imbalances in their expression may have pathological outcomes ( Abel et al, 2021 ). A systematic approach was employed to isolate miRNAs regulating the NRP1 gene.…”
Section: The Influence Of Micrornas On Neuropilin-1 In Preeclampsia H...mentioning
confidence: 99%
“…Houzet et al observed a decrease in the nef mRNA and viral load that positively correlated with miR-29a suppression [ 118 ]. The decrease in miR-29a in HIV could be a compensatory mechanism to maintain the latent state of infection [ 11 , 119 ]. MiR-16 is upregulated in PE and COVID-19 but downregulated in HIV infection [ 18 , 114 ].…”
Section: The Involvement Of Vegfr-2-specific Micrornas In Preeclampsi...mentioning
confidence: 99%
“…During the COVID-19 (coronavirus disease 2019) lockdown, maternal deaths increased by 30% in SA [ 8 ]. Reportedly, the duality of PE and HIV infection increases susceptibility to SARS-CoV-2 infection and the triad of diseases impacts inflammatory responses and endothelial function [ 10 , 11 ]. It is vital to ascertain the conceptual framework underlying the interaction of PE, HIV infection, cART usages, and SARS-CoV-2 infection in order to prevent maternal deaths.…”
Section: Introductionmentioning
confidence: 99%